PELAKSANAAN PERSIDANGAN DENGAN TERDAKWANYA ANAK DI INDONESIA - Berlian S.H., M.Hum (Universitas Quality, 2019)
Children as the nation's next generation is already deserve special attention. It aims in order to develop the child to realize the quality of human resources. Therefore, it is also necessary legal infrastructure to anticipate any problems that arise. The legal means to anticipate stigma or stamp evil inflicted when the child against the law, as well as restoring and re-socialize the child. One solution is to divert or placing the offender children out of the criminal justice system as well as providing an alternative to the settlement with justice approach in the best interests of the child, who was then known as restorative justice approach. Restorative justice which is the implementation of the concept of diversion has been formulated in the juvenile justice system, but a good system must be accompanied by an attitude which is imbued with the will to perceive and believe that this world is always getting better. In addition, should the principle of the best interest of the children always come first when dealing with children in conflict with the law.